Electrochemical Sensors for the Detection of Reactive Oxygen Species in Biological Systems: A Critical Review - Geraskevich A. V. Alina Vadimovna; Solomonenko A. N. Anna Nikolaevna; Dorozhko E. V. Elena Vladimirovna; Korotkova E. I. Elena Ivanovna; Barek J. Jiri (2022, 2022)
Title screen